EFEKTIVITAS LACTOBACILLUS SPOROGENEUS TERHADAP PENURUNAN INTOLERANSI GLUKOSA PADA MENCIT JANTAN GALUR SWISS WEBSTER - Yedy Purwandi (Jurnal Kesehatan Bakti Tunas Husada: Jurnal Ilmu-ilmu Keperawatan, Analis Kesehatan dan Farmasi, 2015)
Problem health or Disease has change from infectious disease become degenerative disease. This change stimulated by life style, environment and genetics. Diabetes Mellitus is one of degenerative disease. Therefore, researcher implement research to evaluated reduction glucose intolerance effect of Lactobacillus sporogenes. Test Group Male swiss webster mice given orally Lactobacillus sporogenes suspension for 7 days with dosage used are 12 x 106/Kg BW, 24 x 106/Kg BW and 48x 106/Kg BW.  Afterward, given dexamethason (20 mg /Kg BW) intraperitoneally for 4 days. Reduction blood glucose concentration evaluated in 0, 30, 60 and 120 minute after given glucose at dosage 1.5 g/Kg BW. The results showed that all dose above, given significant (p<0.05) reduction glucose intolerance. Therefore, Lactobacillus sporogenes may potensial as a preventive for Glucose intolerance. However, further studies still required.Key words:  Diabetes Mellitus, Lactobacillus sporogenes , Glucose intolerance